Computer-based marketing exercises: Marketing / Joel R. Evans, Barry Berman, John C. Galoway - Evans, Berman[et.al] (1987)
Computer requirements, computer -based marketing exercises, Boston consulting group, explanation of exercise, problem / opportunity assessment, end use analysis product screening, tatal cost approach,reorder point analysis, economic order quantity, advertising budget, price alasticity, competitive bidding, allocating funtional costs